PERAN UNIT PELAKSANA TEKNIS (UPT) INDUSTRI KULIT DAN PRODUK KULIT MAGETAN DALAM PEMBERDAYAAN PENYAMAK KULIT DI KABUPATEN MAGETAN - sofia rizky purwanto; puji astuti; lusia astrika (Journal of Politic and Government Studies, 2016)
Tanning industry is one of the regional potential in Magetan which has existed since the end of the Diponegoro War (± 1830), the tanning industry have helped support the leather industry. But in the years 1960-1970 the tanning industry has declined and nearly died because they were unable to compete with the plastics industry. To cope the situation the Local Government Magetan . UPT Industry Leather and Leather Products Magetan aims to build through the empowerment to the tanners, either through economic empowerment and community empowerment. From this, the researchers will examine what role are being made by UPT Industry Leather and Leather Products Magetan in the empowerment of tanners in Magetan.This study aims to determine the role of UPT Industry Leather and Leather Products Magetan in empowering tanner. This type of research is descriptive qualitative analytic approach and methods used are interviews, literature, documentation, and observation.The results of this study are UPT Industry Leather and Leather Products Magetan can carry out its role properly so as to provide updates to the tanner both economically and socially. Various role of UPT Industry Leather and Leather Products in empowering tanners in Magetan can be seen from the four role that has been played by, among others, (1) Facilitative Roles and Skills, (2) Educational Roles and Skills, (3) Representatif Roles and Skills, and (4) Technical Roles and Skills.Research has been conducted to provide information that the empowerment of tanners in Magetan, UPT Industry Leather and Leather Products Magetan have contributed and perform the duties and functions in accordance with its working area. However, one thing that needs to be underlined is that basically the leather tanning industry needs a regulation that gives special attention to the tanning industry. Therefore, the leather tanning industry is not only focused on the existence of the tanning products but also on the waste produced. That way, when problems arise and threaten indicate the tanning industry in Magetan can be solved.Keywords: Role of UPT, Empowerment, Tanners